DAMPAK GAME ONLINE TERHADAP MOTIVASI BELAJAR DAN PRESTASI AKADEMIK ANAK DENGAN METHODE KUALITATIF - Bani, Bani; Maulida, Rusyda; Puspitasari, Tita (LPPM STMIK Antar Bangsa, 2025)
Abstract– In the context of rapid technological development, online games have become a global phenomenon dominating the leisure time of children and adolescents. These games, with their engaging and interactive designs, often become an essential part of their daily routines. While many acknowledge the entertainment and social potential of online games, their impact on children's learning motivation and academic achievement remains poorly understood. While quantitative studies have provided data on the relationship between online games and academic outcomes, qualitative methods offer a more in-depth perspective on children's subjective experiences in this context. Qualitative methods, through techniques such as in-depth interviews, focus group discussions, and observation, allow researchers to explore the nuances and complexities of children's experiences with online games. This study aims to explore how online games affect their learning motivation, how they balance their time between gaming and study, and how their perceptions of education may be affected by gaming engagement. With this approach, it is hoped that various factors influencing the relationship between online games and academic achievement can be identified, such as the type of game played, the duration of play, and the social context in which the play occurs.